Postura e biomecânica da coluna vertebral em crianças com asma - Silva, Ada Cristina Jácome Sarmento (2021)
Introduction: Obstructive conditions, such as asthma, can cause respiratory muscle overload due to excessive use of accessory muscles, resulting in functional impact and changes in muscle length. Objective: To assess and compare posture and biomechanics (range of motion and muscle strength) of the spine of children with asthma. Methods: This is an exploratory comparative study that evaluated children aged 7 to 12 years with a clinical diagnosis of asthma and healthy children, matched for age, sex, and height. Anthropometric, posture, range of motion, cervical and thoracolumbar muscle strength, spirometry and assessment of clinical control were performed. Results: The study consisted of 41 children with asthma and 21 healthy schoolchildren. Posture (sagittal angle of the head, cervical angle, shoulder angle and thoracic kyphosis) and biomechanics (range of movement and muscle strength) of the cervical and thoracolumbar spine were compared between the participants with asthma according to the clinical control of the disease (asthma controlled / controlled controlled, uncontrolled asthma) and with healthy schoolchildren. There was no difference (p>0.05) in posture (sagittal head angle, cervical angle, shoulder angle and thoracic kyphosis) between groups. Variables range of motion of cervical spine extension and thoracolumbar spine extension showed significant differences between the controlled/partially controlled, uncontrolled and healthy asthma groups (p <0,05). Conclusions: The variables of posture of the cervical and thoracolumbar spine did not differ between children with asthma and healthy schoolchildren. Children with controlled/partially controlled and uncontrolled asthma have a lower range of motion of cervical spine extension when compared to healthy children. Otherwise children with uncontrolled asthma have a lower range of motion of the thoracolumbar spine compared to children with controlled/partially controlled asthma and school children healthy.